2012
DOI: 10.1111/j.1872-034x.2012.00996.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and liver disease

Abstract: In humans, oxidative stress and antioxidant defenses are the sum of a complicated network of enzymatic and non-enzymatic processes. Depending on the stage and severity of diseases, a patient's antioxidant armamentarium may increase as an appropriate response to an oxidant challenge, whereas others may decrease as an indication of unbalanced consumption. In some cases, the formation of reactive oxygen species is a requisite and healthy event. In fact, free radicals can affect intracellular signal transduction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(140 citation statements)
references
References 73 publications
(120 reference statements)
6
129
0
5
Order By: Relevance
“…The obtained results were in parallel with Zhu et al(2012) found that Post-transplant parenteral nutritional support combined with omega-3 fatty acids can significantly improve the liver in jury, reduce the infectious morbidities, and shorten the post-transplant hospital stay.…”
Section: Effect Of Pizza Supplemented With Different Levels Of Fish Osupporting
confidence: 77%
“…The obtained results were in parallel with Zhu et al(2012) found that Post-transplant parenteral nutritional support combined with omega-3 fatty acids can significantly improve the liver in jury, reduce the infectious morbidities, and shorten the post-transplant hospital stay.…”
Section: Effect Of Pizza Supplemented With Different Levels Of Fish Osupporting
confidence: 77%
“…30) As seen by our results, during hepatotoxicity, these enzymes are structurally and functionally impaired by an overload of free radicals, resulting in dysfunction. 31) BCA restored their levels and even boosted their activities at higher doses. A similar effect was seen in the level of GR, which was significantly decreased by CCl 4 and boosted by BCA administration.…”
Section: Discussionmentioning
confidence: 99%
“…However, the excessive formation of ROS and their reactive derivatives induces oxidative stress, which is associated with different chronic pathologic conditions, including cancer as well as liver diseases (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%